Applying an Implementation Science Framework to Extreme Risk Protection Orders. - Geller, Lisa B.; Cantrell, Spencer M. (Inquiry (00469580), 2025)
Twenty-one states, the District of Columbia, and the U.S. Virgin Islands have Extreme Risk Protection Orders (ERPOs), with most states enacting them after the preventable mass shooting in Parkland, Florida in 2018. ERPO laws are an evidence-informed policy to curb the public health crisis of gun violence in the United States as they provide a legal mechanism to temporarily restrict access to firearms when an individual is exhibiting dangerous behaviors. This paper utilizes a well-known implementation science framework proposed by Proctor et al to evaluate implementation outcomes for ERPO laws. The framework identifies 8 components of implementation—adoption, acceptability, appropriateness, cost, feasibility, fidelity, penetration, and sustainability—which are examined in the context of ERPO implementation. By viewing the implementation process through this framework, we highlight both the successes and the gaps in ERPO implementation, with the aim of improving implementation moving forward. Each of the 8 steps in Proctor's evaluation framework are critical to the success of ERPO laws. First, a law that has not been adopted cannot be implemented; therefore, passing ERPO laws are critical. Typically, only laws deemed "acceptable" by most lawmakers, and ideally the public, are passed. ERPO is an appropriate tool for addressing gun violence, satisfying the third prong of the framework. Costs can be mitigated to improve feasibility. Most ERPO laws have fidelity to its original mission. ERPO programs have penetrated many state entities' infrastructure. Promising practices from around the country demonstrate how the law can be sustained through dedicated funding and support. A law that is not implemented cannot be successful. By focusing on robust implementation of ERPO based on promising practices across the country, implementers can increase the likelihood of success and save lives.